Biodegradeable temporising matrix use in a traumatic chest wound. Issue 12 (20th December 2021) - Carrington-Windo, Eliot; Leong, Sam; Ibrahim, Nader; Pope-Jones, Sophie
Abstract : The Welsh Centre for Burns and Plastic Surgery is responsible for a population of 10 million people in Wales and England. We describe the use of biodegradable temporising matrix (BTM) in a large traumatic chest wound in a 23-year-old woman. BTM is a synthetic dermal substitute and has been utilised to achieve soft tissue coverage in complex wounds. This wound was sustained after the patient fell from a tractor into a large silage rake, resulting in injuries to her chest and limbs. Following meticulous debridement, her resulting full thickness skin defect measured 30 × 30 cm extending from the sternal notch to the upper abdomen, with bone, muscle and breast tissue exposure. The central chest area is complex to reconstruct due to the contours of the breasts and tendency to contracture following skin graft reconstruction. We demonstrate the first reported use of BTM for breast reconstruction, as far as we are aware.